The autologous chondral platelet-rich plasma matrix implantation. A new therapy in cartilage repair and regeneration: macroscopic and biomechanical study in an experimental sheep model - Peláez-Gorrea, Pau; Damiá-Giménez, Elena; Rubio-Zaragoza, Mónica; Cuervo-Serrato, Belén; Hernández-Guerra, Ángel María; Miguel-Pastor, Laura; Del Romero-Martínez, Ayla; Sopena-Juncosa, Joaquín; Torres-Torrillas, Marta; Santana, Angelo; Cugat-Bertomeu, Ramón; Vilar-Guereño, José Manuel; et al. (Frontiers in Veterinary Science, 2023)
Introduction: Articular cartilage injuries are a severe problem, and the treatments for these injuries are complex. The present study investigates a treatment for full-thickness cartilage defects called Autologous Chondral Platelet Rich Plasma Matrix Implantation (PACI) in a sheep model. Methods: Chondral defects 8 mm in diameter were surgically induced in the medial femoral condyles of both stifles in 8 healthy sheep. Right stifles were treated with PACI and an intraarticular injection with a plasma rich in growth factors (PRGF) solution (treatment group (TRT)), while an intraarticular injection of Ringer's lactate solution was administered in left stifles (Control group (CT)). The limbs' function was objectively assessed with a force platform to obtain the symmetry index, comparing both groups. After 9 and 18 months, the lesions were macroscopically evaluated using the International Cartilage Repair Society and Goebel scales. Results: Regarding the symmetry index, the TRT group obtained results similar to those of healthy limbs at 9 and 18 months after treatment. Regarding the macroscopic assessment, the values obtained by the TRT group were very close to those of normal cartilage and superior to those obtained by the CT group at 9 months. Conclusion: This new bioregenerative treatment modality can regenerate hyaline articular cartilage. High functional outcomes have been reported, together with a good quality repair tissue in sheep. Therefore, PACI treatment might be a good therapeutic option for full-thickness chondral lesions.